Structural design of an oil tanker using primeship - bosun - 221622 Koh, Kho King (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering (Marine Technology)) - Universiti Teknologi Malaysia, 1999